Artificial intelligence and digital art: current state and development prospects - Марія Чікарькова (Cхід)
The article analyzes the use of artificial intelligence in various types of digital art at the current level of their development and outlines the possibilities of external ways of such interaction. The author considers specific artistic examples, which see that the use of artificial intelligence in art develops a complex art history and philo-sophical questions: what is art? how does computer technology change aesthetics? where is the line between technology and creativity? who is considered the author of the work generated by neuronets? is it possible to compare anthropocentric and non-anthropocentric forms of creativity? etc. The researcher demonstrates different approaches to the chosen topic, citing antagonistic points of view of scientists. Some of them believe that art with the help of a computer is the next step in the development of avant-garde trends, while others see these trends as the degradation and even the death of art. In digital painting, we are already faced with the use of works (the most famous example is the android-artist Ai-Da) who know how to draw in different techniques and with the use of different tools. The victory of a painting generated by a neural network at an art competition raised questions about its au-thorship and the admissibility of participation of such works in competitions for art-ists. Discussions on the ArtStation platform indicate that many artists do not per-ceive works made with the help of artificial intelligence as "real" works of art. In mu-sic today, it is possible not just to generate melodies, but to create an imitation of certain styles or composers, which raises questions about the nature of true creativi-ty and its limits. Another direction of using artificial intelligence in music is the crea-tion of virtual singers who become mega-popular. Such an example is given by the Japanese virtual singer Hatsune Miku, who is a hologram with an android interface and an artificially generated voice. In the field of video games, artificial intelligence knows how to create not only levels, but already generate game target worlds and complete games. Artificial intelligence in photography can generate images of non-existent people. At the same time, it is unlikely that artificial intelligence can com-pletely replace a human artist, after which he learns from the previously created ma-terial. This makes it possible to say that he left real creativity and knows how to compile in advance, and not to generate original artistic solutions.